Nickel oxide catalyst doped noble metals for the conversion of carbon dioxide to methane - Tan, Chia Ling, 1987-; Wan Azelee Wan Abu Bakar; Fakulti Sains (2010)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2010